Contrasting impacts of different-sized herbivores on species richness of Mediterranean annual pastures differing in primary productivity. - Rueda, Marta; Rebollo, Salvador; García-Salgado, Gonzalo (Oecologia, 2012)
Vertebrate herbivores can be key determinants of grassland plant species richness, although the magnitude of their effects can largely depend on ecosystem and herbivore characteristics. It has been demonstrated that the combined effect of primary productivity and body size is critical when assessing the impact of herbivores on plant richness of perennial-dominated grasslands; however, the interaction of site productivity and herbivore size as determinants of plant richness in annual-dominated pastures remains unknown. We experimentally partitioned primary productivity and herbivore body size (sheep and wild rabbits) to study the effect of herbivores on the plant species richness of a Mediterranean semiarid annual plant community in central Spain over six years. We also analyzed the effect of grazing and productivity on the evenness and species composition of the plant community, and green cover, litter, and plant height. We found that plant richness was higher where the large herbivore was present at high-productivity sites but barely changed at low productivity. The small herbivore did not affect species richness at either productivity site despite its large effects on species composition. We propose that adaptations to resource scarcity and herbivory prevented plant richness changes at low-productivity sites, whereas litter accumulation in the absence of herbivores decreased plant richness at high productivity. Our results are consistent with predictions arising from a long history of grazing and highlight the importance of both large and small herbivores to the maintenance of plant diversity of Mediterranean annual-dominated pastures.
Keywords: Body size; Dehesa; european rabbits; Grazing; plant-herbivore